Trauma Related to Road Traffic Accidents at the Abéché University Hospital (Chad): Epidemiological and Injury Patterns in a Series of 972 - Younous Adoum Seid; Oumar Aboulghassim; Allamine Hassan Adoum; Mahamat Annour Ali Mahadi; Sadie Ismael Guire; Moussa Kalli; Oumar Bachar Loukoumi; Hemchi Hisseine Sougou; Choua Ouchemi (European Scientific Journal, ESJ, 2026)
Introduction: To describe the epidemiological profile, injury patterns, therapeutic management, and outcomes of road traffic accident (RTA)-related injuries managed at the Abéché University Hospital Center in eastern Chad. Patients and methods: This was a retrospective descriptive study conducted over a 12-month period, from September 1, 2023, to August 31, 2024.  Results: This study included 972 patients admitted for RTA-related injuries out of 2,750 consultations, corresponding to a hospital frequency of 35.34%.The mean age of patients was 26.5 years, with the 21–30-year age group being the most represented (41.6%). Males predominated (82.1%), with a male-to-female ratio of 4.59. Students and pupils were the most affected socio-professional group (44.96%). Tricycle–motorcycle collisions were the most frequent mechanism of injury (51.75%). The most common lesions were dermabrasions (41.36%) and limb injuries (40.53%), mainly fractures. Head injuries accounted for 4.22% of cases, while polytrauma was observed in 3.60%. Management consisted mainly of local wound care (41.36%), orthopedic treatment (12.65%), and surgical intervention (9.57%). A high rate of discharge against medical advice was noted (24.69%). Overall hospital mortality was 9.53%, occurring predominantly in patients with severe head injuries and polytrauma. Conclusion: Road traffic accidents represent a major public health concern in the province of Abéché, predominantly affecting young men. Collisions involving tricycles and motorcycles are the leading cause of injury and are associated with severe trauma and high mortality. Strengthening road safety measures, improving prehospital medical transport, and upgrading hospital technical facilities, particularly critical care services, are essential to reduce RTA-related morbidity and mortality.